Analysis of the influence of the thickness insufficiency in secondary lining on the mechanical properties of Double-layer lining of shield tunnel. (November 2022) - Wang, Shimin; Wang, Ya; Lin, Zhiyu; Song, Zihan; Wang, Xianming; Peng, Xiaoyu
Highlights: The failure mode of double-layer lining structure with defect is revealed. Bearing Performance of double-layer lining structure with defect is revealed. A thickness control standard of secondary lining defects is proposed. Abstract: Difficulties such as large burial depth, large cross-section, and high water pressures exist in the construction of underwater shield tunnels. Thus, the double-layer lining structure begins to be one means of reinforcement of tunnels. To figure out how the depth of the insufficient thickness in the vault of the segment's secondary lining influences the entire structure, the Rail-cum-Road Yangtze River Cross Tunnel in Wuhan is taken as an example, where the deformation distribution, internal force characteristics and failure process of the double-layer lining structure caused by the thickness insufficiency are revealed through a model test method.